A novel stop mutation (p.(Gln22*)) of DAX1 (NR0B1) results in late-onset X-linked adrenal hypoplasia congenita. (4th September 2017) - Gerards, Judith; Ritter, Michael M; Kaminsky, Elke; Gal, Andreas; Hoeppner, Wolfgang; Quinkler, Marcus
Summary: DAX1 (NR0B1) is an orphan nuclear receptor, which plays an important role in development and function of the adrenal glands and gonads. Mutations in DAX1 cause X-linked adrenal hypoplasia congenita (X-linked AHC), which is characterized by adrenal insufficiency (AI) and hypogonadotropic hypogonadism (HHG). Affected boys present with adrenal failure usually in childhood and, later in life, with delayed puberty. However, patients with a late-onset form of X-linked AHC have also been described in the past years. We report a male patient who presented with symptoms of an adrenal crisis at the age of 38 years and was later diagnosed with HHG. Family history was positive with several male relatives diagnosed with AI and compatible with the assumed X-chromosomal inheritance of the trait. Direct sequencing of DAX1 of the patient revealed a hemizygous cytosine-to-thymine substitution at nucleotide 64 in exon 1, which creates a novel nonsense mutation (p.(Gln22*)). In order to compare the clinical presentation of the patient to that of other patients with X-linked AHC, we searched the electronic database MEDLINE (PubMed) and found reports of nine other cases with delayed onset of X-linked AHC. In certain cases, genotype–phenotype correlation could be assumed. Learning points: X-linked AHC is a rare disease characterized by primary AI and hypogonadotropic hypogonadism (HHG). The full-blown clinical picture is seen usually only in males with a typical onset in childhood. Patients with a late-onset form of X-linked AHC have also been described recently. Being aware of this late-onset form might help to reach an early diagnosis and prevent life-threatening adrenal crises. Adult men with primary AI of unknown etiology should be investigated for HHG. Detecting a DAX1 mutation may confirm the clinical diagnosis of late-onset X-linked AHC. In relatives of patients with genetically confirmed X-linked AHC, targeted mutation analysis may help to identify family members at risk and asymptomatic carriers, and discuss conscious family planning.